The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.5007/1980-0037.2010v12n1p8
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre a retirada e reativação vagal com a capacidade aeróbia em atletas de taekwondo DOI:10.5007/1980-0037.2010v12n1p8

Abstract: -The aim of this study was to evaluate the relationship between vagal withdrawal and reactivation indices and maximal running velocity (Vmax) ) performed a graded exercise test until exhaustion, with the last complete stage performed corresponding to Vmax. Heart rate variability (HRV) parameters were calculated at 1-minute intervals until 85% of maximum HR and plotted against time for the estimation of vagal withdrawal indices (τ, amplitude (A) and area under the curve (AUC)). Vagal reactivation indices were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It appears that both methods of HRV quantification yield similarly reproducible indices of HRV during exercise. We thought that the time domain parameters would demonstrate a greater reproducibility as these are suggested to be less influenced by non-stationarities in the data (Pagani et al 1988, Perandini et al 2009, Asmussen and Kristiansson 1968). However, it must be noted that quantification of HRV in the frequency-domain requires pre-processing to improve the stability of the RR timeseries, and this might conceivably have improved the repeatability of the frequency-domain HRV measures.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that both methods of HRV quantification yield similarly reproducible indices of HRV during exercise. We thought that the time domain parameters would demonstrate a greater reproducibility as these are suggested to be less influenced by non-stationarities in the data (Pagani et al 1988, Perandini et al 2009, Asmussen and Kristiansson 1968). However, it must be noted that quantification of HRV in the frequency-domain requires pre-processing to improve the stability of the RR timeseries, and this might conceivably have improved the repeatability of the frequency-domain HRV measures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the faster HRR found in the first (HRR60s) and second (HRR120s) minutes after constant load exercise suggests that the beginning of passive recovery is also influenced by withdrawal of sympathetic activity (Danieli et al., 2014). The RMSSD 30s , a non‐stationary HRV index representing vagal modulation, was higher for some minutes after the constant workload exercise (Perandini et al., 2010). In addition, the higher value observed at 120 s may be related to the higher decay of heart rate at the same time in constant workload exercise.…”
Section: Discussionmentioning
confidence: 99%